Critical climate justice - Sultana, Farhana (The Geographical journal, 2022)
Climate change has had unequal and uneven burdens across places whereby the planetary crisis involves a common but differentiated responsibility. The injustices of intensifying climate breakdown have laid bare the fault lines of suffering across sites and scales. A climate justice framework helps us to think about and address these inequities. Climate justice fundamentally is about paying attention to how climate change impacts people differently, unevenly, and disproportionately, as well as redressing the resultant injustices in fair and equitable ways. Critical climate justice as a praxis of solidarity and collective action benefits from greater engagement with intersectional and international feminist scholarship. Incorporating insights from feminist climate justice bolsters solidarity praxis while enriching and reframing dominant climate change discussions for more impactful and accountable action. Climate change has had unequal and uneven burdens across places whereby the planetary crisis involves a common but differentiated responsibility. Climate justice fundamentally is about paying attention to how climate change impacts people differently, unevenly, and disproportionately, as well as redressing the resultant injustices in fair and equitable ways. Critical climate justice as a praxis of solidarity and collective action benefits from greater engagement with intersectional and international feminist scholarship.